Supply chain collaboration to reduce food loss and waste : a multi-case study of Swedish bread suppliers and retailers - Bergman, Linn; Holmqvist, Jessica (SLU/Dept. of Economics, 2022)
Food loss and waste is an urgent and important sustainability problem that needs to be addressed both globally and locally. This study focuses on understanding preconditions for supply chain collaboration to reduce food loss and waste in the suppliers-retailer interface. A multi-case study of Swedish bread suppliers and retailers was conducted by interviewing two Swedish bread suppliers and two Swedish bread retailers. The study identified preconditions for supply chain collaboration in terms of practices, motives and challenges. The study concluded that suppliers and retailers identify similar and different preconditions for supply chain collaboration to reduce food loss and waste. Foremost, information sharing, used to produce more accurate forecasts, is seen as a promising supply chain collaboration practice for both suppliers and retailers. Improving business performances, focusing on economic incentives, is an important supply chain collaboration motive. Lastly, supply chain collaboration challenges are mostly centered around power asymmetries between the suppliers and retailers. The study also indicated that supply chain collaboration is context dependent. Thus, creating different preconditions for supply chain collaboration for suppliers and retailers depending on the social context. Moreover, the identified supply chain collaboration practices, motives and challenges are all influenced and connected to one another. Hence, supply chain collaboration was found to be more complex in practice than as illustrated in previous research. For future studies, it would therefore be interesting to investigate supply chain collaboration between a plurality of actors and not only suppliers and retailers. More research is also needed in other food supply chains with particular focus on how such collaborations are functioning in practice. This would contribute to an increased academic and empirical understanding of supply chain collaboration to reduce food loss and waste in food supply chains, which remains a critical issue.